2020
DOI: 10.1021/acs.orglett.0c01517
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Intramolecular C–H Alkoxylation of Diaryltriazoles: Synthesis of Tricyclic Triazole Benzoxazines

Abstract: An efficient copper-catalyzed intramolecular C-H alkoxylation of 1,4-disubstituted 1,2,3-triazoles has been developed. The chemistry was applied to a wide range of substrates, generating tricyclic benzoxazine-fused 1,2,3-triazoles in good yields. Mechanistic studies suggest that a radical pathway may be involved in this transformation. The triazole products were found to exhibit strong antifungal activity against ginseng root-rot disease, demonstrating their potential as a scaffold in medicinal chemistry resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Recently, CuAAC derived triazoles in the presence of Cu­(I) catalysis have been reported to undergo C(5)–H activation via intramolecular C–H alkoxylation through a radical route and give high-to-excellent yield of tricyclic triazoles displaying potent antifungal activity . Although, similar C–H activation can also be achieved easily by utilizing the carbohydrate-based triazoles, surprisingly little effort has been made so far in this direction.…”
Section: Cuaac Carbo-click In Sensing Gelation Chelation Glycosylatio...mentioning
confidence: 99%
“…Recently, CuAAC derived triazoles in the presence of Cu­(I) catalysis have been reported to undergo C(5)–H activation via intramolecular C–H alkoxylation through a radical route and give high-to-excellent yield of tricyclic triazoles displaying potent antifungal activity . Although, similar C–H activation can also be achieved easily by utilizing the carbohydrate-based triazoles, surprisingly little effort has been made so far in this direction.…”
Section: Cuaac Carbo-click In Sensing Gelation Chelation Glycosylatio...mentioning
confidence: 99%
“…Notably, 6-endo cyclization was preferred over the 5-exo cyclization irrespective of the substituents present in the alkenes. Later, Jiang and co-workers reported the synthesis of tricyclic triazole-benzoxazines through copper-catalyzed intramolecular triazole C–H alkoxylation (Scheme e) . The antifungal properties of the synthesized compounds were tested against F. oxysporum , F. solani , and C. destructans and showed promising levels of inhibition of F. oxysporum compared to existing antifungal agents…”
Section: Hydroxy-directed C–h Bond Functionalizationsmentioning
confidence: 99%
“…Later, Jiang and coworkers reported the synthesis of tricyclic triazole-benzoxazines through copper-catalyzed intramolecular triazole C−H alkoxylation (Scheme 105e). 207 The antifungal properties of the synthesized compounds were tested against F. oxysporum, F. solani, and C. destructans and showed promising levels of inhibition of F. oxysporum compared to existing antifungal agents In 2015, Wang and co-workers reported a straightforward synthesis of coumarin via carbonylation of vinylphenol using carbon monoxide (Scheme 106). 208 They utilized Cp*Co-(CO)I 2 as catalyst along with Ag 2 CO 3 and Cu(OAc) 2 as oxidant as well as carboxylate source.…”
Section: Ester-directed C−h Bond Functionalizationsmentioning
confidence: 99%
“…Li and co-workers synthesized tricyclic triazole-benzoxazines 223 through copper-mediated intramolecular C-H alkoxylation of 1,4-disubstituted 1,2,3-triazoles 224 (Scheme 85). 96 This new methodology has extensive application in the eld of medicinal and agro chemistry. It was observed that the 1,4-disubstituted 1,2,3-triazoles with electron-donating and electron-withdrawing groups were well tolerated in this reaction.…”
Section: C-o Bond Formationmentioning
confidence: 99%